LIMA DUARTE, Constância (Org.). Nísia Floresta: a primeira feminista do Brasil. - Knorr, Eliane (Revista Estudos Feministas, 2006)
LIMA DUARTE, Constância (Org.). Nísia Floresta: a primeira feminista do Brasil.